2000
DOI: 10.1034/j.1600-051x.2000.027008558.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic effects of ketoprofen on crevicular fluid prostanoids in adult periodontitis

Abstract: The reported therapeutic benefits of nonsteroidal anti-inflammatory drugs (NSAIDs) in slowing periodontal disease progression appear intimately linked to the effective inhibition of local prostaglandin synthesis. This randomized, partially double-blind, controlled trial was conducted to evaluate the pharmacodynamic effects of the NSAID, ketoprofen (KTP), on gingival crevicular fluid (GCF) prostanoids. 42 subjects, ages 35-57 years, with moderate to advanced adult periodontitis were recruited and monitored for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…The authors observed that the administration of higher doses of this drug yielded a reduction of the area of cancellous bone and an increase in bone trabeculae. Paquette et al (2) evaluated the The results of the present study do not agree with those of the above-mentioned investigations (2,4,20). Unlike these authors, we have observed that the dosage and period of administration of a NSAID directly interfered with its mechanism of action because OD values of the unicortical bone defects created in tibiae of rats increased in both ketoprofen-treated (daily oral dose of 12.5 mg/kg for 30 days) and control groups up to the 21st day, with greater OD values for the ketoprofen group.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The authors observed that the administration of higher doses of this drug yielded a reduction of the area of cancellous bone and an increase in bone trabeculae. Paquette et al (2) evaluated the The results of the present study do not agree with those of the above-mentioned investigations (2,4,20). Unlike these authors, we have observed that the dosage and period of administration of a NSAID directly interfered with its mechanism of action because OD values of the unicortical bone defects created in tibiae of rats increased in both ketoprofen-treated (daily oral dose of 12.5 mg/kg for 30 days) and control groups up to the 21st day, with greater OD values for the ketoprofen group.…”
Section: Discussioncontrasting
confidence: 97%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) are competitive inhibitors of the cyclooxygenase enzyme (COX), which is in charge of the biosynthesis of prostaglandins and thromboxanes from the arachidonic acid (1)(2)(3). Two forms of the cyclooxygenase enzyme have been described, COX-1 and COX-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of KLS to modulate the bronchoconstriction induced by BK and to a larger extent the increase in airway permeability induced by BK has been reported to depend on cyclooxygenase blockade [16]. In this regard, topical ketoprofen has been recently shown to reduce gingival crevicular fluid prostaglandin E 2 levels in adult periodontitis [17] and to reduce the rate of alveolar bone loss in monkeys with ligature-induced oral inflammation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding NSAID efficacy period, it has been shown that the inhibitory effect of PGE 2 continues only during drug intake phase and will end after drug therapy cessation (13). In this short-term evaluation, PD and BOP presented significant improvement during the observation period.…”
Section: Discussionmentioning
confidence: 66%